The Significance of Selected Socio‑Economic Factors for Formation of the Fiscal Sustainability of Cities in Poland - Wójtowicz, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The article attempts to assess the impact of selected economic and social factors on the fiscal sustainability of cities in Poland. The research sample covered 241 such local government units, and the time range was 2004–2016. The article uses the econometric modeling of panel data. The analysis revealed that the extent of the relationship between the economic and social development of local governments and their financial health proved to be significantly lower than could be expected. The possible cause of this situation seems to be the dependence of local budgets on external grants and the high share of fixed expenditure, as well as the existence of “soft budget constraints”, which guarantee the aid form central budget in case of insolvency.